A Comparison of Social Stories with and without Video Modeling in Teaching How to Respond to Lures of Strangers to Children with Autism - Onur Kurt; Metehan Kutlu (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: The purpose of this study was to compare the effectiveness and efficiency of social stories with and without video modeling in teaching how to respond to lures of strangers to children with autism.Method: The study was conducted with four children aged 10-13 years diagnosed with autism. Target skills for the students were how to avoid abduction by strangers and how to respond if a stranger knocked at the door. An adapted alternating treatments design was used in the study.Findings: The findings of the study showed that both procedures were equally effective on promoting acquisition for three of the four students with autism. The findings showed that social stories alone was more effective than social stories with video modeling for one student. There was no considerable difference between the two procedures in terms of efficiency. Social validity findings showed that opinions of the participants and their mothers were positive overall.Discussion: It is likely appropriate for teachers, researchers, practitioners, and families to use only one of the teaching practices compared in this study, taking into account the characteristics and preferences of their students in teaching the skills of protection from strangers. To generalize the findings from this study, it can be suggested that similar studies be conducted with different practitioners and participants in various age groups.